Can gender difference in prescription drug use be explained by gender-related morbidity?: a study on a Swedish population during 2006 - Skoog, Jessica (BioMed Central, 2014)
BACKGROUND: It has been reported that there is a difference in drug prescription between males and females. Even after adjustment for multi-morbidity, females tend to use more prescription drugs compared to males. In this study, we wanted to analyse whether the gender difference in drug treatment could be explained by gender-related morbidity. METHODS: Data was collected on all individuals 20 years and older in the county of Östergötland in Sweden. The Johns Hopkins ACG Case-Mix System was used to calculate individual level of multi-morbidity. A report from the Swedish National Institute of Public Health using the WHO term DALY was the basis for gender-related morbidity. Prescription drugs used to treat diseases that mainly affect females were excluded from the analyses. RESULTS: The odds of having prescription drugs for males, compared to females, increased from 0.45 (95% confidence interval (CI) 0.44-0.46) to 0.82 (95% CI 0.81-0.83) after exclusion of prescription drugs that are used to treat diseases that mainly affect females. CONCLUSION: Gender-related morbidity and the use of anti-conception drugs may explain a large part of the difference in prescription drug use between males and females but still there remains a difference between the genders at 18%. This implicates that it is of importance to take the gender-related morbidity into consideration, and to exclude anti-conception drugs, when performing studies regarding difference in drug use between the genders.